İŞ TATMİNİ ÜZERİNE OLAN MAKALELERİN WEB OF SCİENCE VERİ TABANINDA BİBLİYOMETRİK ANALİZİ. - CEYLAN, Ali Kemal (International Anatolian Journal of Social Sciences / Uluslararasi Anadolu Sosyal Bilimler Dergisi)
Organizations are becoming increasingly diverse and complex as a result of globalization, which has significantly influenced human resource management practices. Employee needs, motivations, and job satisfactions have become central concerns in managing organizational behavior. Job satisfaction has been widely studied due to its substantial impact on employee performance and organizational outcomes. Bibliometric analysis, a research method based on statistical techniques, identifies publication trends and relationships among studies within a particular field. Several bibliometric studies on job satisfaction have been conducted both in Turkey and internationally, focusing on various sectors and academic theses. In this study, a bibliometric analysis of job satisfaction was carried out at the article level using the Web of Science (WoS) database, both globally and within the context of Turkey. The purpose was to include high-quality studies and to examine the characteristics of publications related to job satisfaction according to several criteria. Network maps of keywords associated with job satisfaction were generated using the VOSviewer software. The analysis revealed that job satisfaction is most frequently associated with burnout (N = 29) in the network structure. Furthermore, the study aimed to reveal the characteristics of academic publications on job satisfaction through analyses such as publication trends by year, country distribution, classification according to the United Nations Sustainable Development Goals (UN SDGs), and identification of the most productive authors.